How using a paper versus mobile calendar influences everyday planning and plan fulfillment - Huang, Yanliu; Yang, Zhen; Morwitz, Vicki G. (Journal of Consumer Psychology, 2023)
AbstractThis research examines how using a paper versus mobile calendar influences everyday planning and plan fulfillment behavior. Consumers are rapidly moving from paper to mobile calendars for convenience, but this research shows that doing so may lead individuals to be less successful in effectively developing and implementing their plans. In three studies, we demonstrate that compared with mobile calendar users, paper calendar users develop higher‐quality plans and are more successful in plan fulfillment. We provide evidence that this happens because paper calendar users take a broader, big‐picture perspective during planning, which also leads to higher‐quality plan development and a greater likelihood of plan fulfillment. When mobile calendar users use a mode that also provides a broader perspective, their plan quality increases.